Manifeste : une histoire parallèle 1960-1990. - Mathey, François; Ceysson, Bernard; Fournier, Jean; Manessier, Alfred; Morellet, François; Jaffe, Shirley; Vallier, Dora; Moulin, Raymonde (Paris : Centre Georges Pompidou, 1993)
Agam ; Alechinsky, Pierre ; Asse, Geneviève ; Bacon, Francis ; Balthus ; Barré, Martin ; Bazaine, Jean ; Bettencourt, Pierre ; Bill, Max ; Burri, Alberto ; Bury, Pol ; Calder, Alexander ; Caro, Anthony ; Chaissac, Gaston ; Cruz-Diez, Carlos ; Debré, Olivier ; Degottex, Jean ; Dewasne, Jean ; Dubuffet, Jean ; Etienne-Martin ; Fontana, Lucio ; Giacometti, Alberto ; Graeser, Camille ; Hantai, Simon ; Hartung, Hans ; Hélion, Jean ; Honegger, Gottfried ; Jacobsen, Robert ; Jaffe, Shirley ; Jorn, Asger ; Kemeny, Zoltan ; Lanskoy, André ; Lapicque, Charles ; Le Moal, Jean ; Leroy, Eugène ; Lohse, Richard-Paul ; Manessier, Alfred ; Matta, Roberto ; Michaux, Henri ; Millares, Manolo ; Miró, Joan ; Mitchell, Joan ; Morellet, François ; Music, Zoran ; Nemours, Aurélie ; Picasso, Pablo ; Poliakoff, Serge ; Rebeyrolle, Paul ; Reigl, Judit ; Riopelle, Jean-Paul ; Saura, Antonio ; Schöffer, Nicolas ; Soto ; Soulages, Pierre ; Stahly, François ; Takis ; Tal-Coat ; Tàpies, Antoni ; Tomasello, Luis ; Ubac, Raoul ; van Velde, Bram ; Vasarely, Victor ; Vieira da Silva, Maria-Elena ; Zao Wou-Ki
Manifeste : une histoire parallèle 1960-1990, Centre Georges Pompidou, Paris, 23 septembre - 13 décembre 1993
boek